2019
DOI: 10.1080/14703297.2019.1617184
|View full text |Cite
|
Sign up to set email alerts
|

The overlooked cohort? – Improving the taught postgraduate student experience in higher education

Abstract: Nutritional Sciences programme where she teaches across a number of human nutrition undergraduate and postgraduate modules. Research interests concern micronutrient deficiencies, in particular the impact of restricted diets on micronutrient status. Pedagogical interests include understanding and improving the education and experience of postgraduate taught students.Rachel Jessop is Director of Internationalisation for the School of Biosciences at the University of Nottingham. Rachel works with staff across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…What is also necessary to note, for our purposes here, is that the evolution of postgraduate habits of mind typically represents, for the students concerned, a metamorphosis-a step-change in learning demands from those encountered in undergraduate studies. The 'challenging negotiations' this transition can call for (Tobbell et al 2010) have been highlighted in various studies (Heussi 2012;West 2012;Mirador 2018;Bamber et al 2019;Coneyworth et al 2020), running counter to the pervasive assumption that the transition to postgraduate study will be unproblematic. Indeed, examining the challenges feedback presents, Scott et al (2014: 134) observed:…”
Section: Postgraduate Habits Of Mind and Feedbackmentioning
confidence: 99%
“…What is also necessary to note, for our purposes here, is that the evolution of postgraduate habits of mind typically represents, for the students concerned, a metamorphosis-a step-change in learning demands from those encountered in undergraduate studies. The 'challenging negotiations' this transition can call for (Tobbell et al 2010) have been highlighted in various studies (Heussi 2012;West 2012;Mirador 2018;Bamber et al 2019;Coneyworth et al 2020), running counter to the pervasive assumption that the transition to postgraduate study will be unproblematic. Indeed, examining the challenges feedback presents, Scott et al (2014: 134) observed:…”
Section: Postgraduate Habits Of Mind and Feedbackmentioning
confidence: 99%
“…Most current EMI studies focus primarily on students at the undergraduate level, but postgraduate students differ from undergraduates in many aspects, including age, educational background, work experiences, learning styles, attitudes, and language proficiency levels [20,21]. The length of undergraduate studies is around three to four years, while a typical postgraduate programme lasts only one to two years, giving students an intensive curriculum and high academic demands [1,11]. Postgraduate students are often assumed to have more expertise, knowledge, and related academic skills than undergraduates, so they may receive less support in their induction into the university [22].…”
Section: Emi At the Postgraduate Levelmentioning
confidence: 99%
“…Postgraduate students are often assumed to have more expertise, knowledge, and related academic skills than undergraduates, so they may receive less support in their induction into the university [22]. A survey of postgraduate students in the UK found that more than 80% of international participants reported challenges in transitioning to their postgraduate studies and the new learning context [11]. The challenges include unfamiliar teaching approaches, language use, and academic writing.…”
Section: Emi At the Postgraduate Levelmentioning
confidence: 99%
See 2 more Smart Citations